Red and black mason wasp, Pachodynerus erynnis (Lepeletier) - Kelly Laplante; Wayne Hobbs; Adam Dale (EDIS)
Pachodynerus erynnis (Lepeletier) is a predatory wasp that specializes in preying upon caterpillars, the larvae of moths and butterflies (Lepidoptera). This insect does not yet have an officially accepted common name and has been referred to as the red and black mason wasp, red-marked Pachodynerus, and a mason wasp. As with other closely related wasps, Pachodynerus erynnis does not form a communal hive, but builds solitary nests in holes or crevices of trees or man-made structures, as well as abandoned nests created by other cavity-nesting bees and wasps. The red and black mason wasp frequently visits flowering plants and can be found entering nesting cavities nearby. This insect is considered highly beneficial because it feeds on several key caterpillar pests, including armyworms (Spodoptera spp.), cutworms (Agrotis spp.), and loopers (Noctuoidea), and has been associated with increased pest control in managed landscapes. Although fairly common, this wasp often goes unnoticed due to its solitary nature and quick flight.